2021
DOI: 10.33225/pec/21.79.412
|View full text |Cite
|
Sign up to set email alerts
|

Intertwining Mathematical Modeling With Environmental Issues

Abstract: Since contemporary learning theories, strategies and models offer the interdisciplinary approach, educators need new pedagogical alternative ways to attain it in practicum. For this reason, the current research aimed to illustrate how to intertwine mathematical modeling with an environmental issue that recruits waste management (e.g., reuse-recycle-reduce) to live an environmentally friendly lifestyle. Through a case study research, 6 seventh-grade students (3 females and 3 males; aged 13-14) voluntarily parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…immigration issues, recycling, and food insecurity. Gürbüz and Çalik (2021) researched 7 th -grade students' investigations of waste management using plastic bottles instead of bricks when building houses. They found that students' dialogues involved discussions both of mathematical problem solving and exploring relevant environmental issues such as protecting the environment, waste saving, and informing society.…”
Section: Combining Sustainability Issues and Mathematical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…immigration issues, recycling, and food insecurity. Gürbüz and Çalik (2021) researched 7 th -grade students' investigations of waste management using plastic bottles instead of bricks when building houses. They found that students' dialogues involved discussions both of mathematical problem solving and exploring relevant environmental issues such as protecting the environment, waste saving, and informing society.…”
Section: Combining Sustainability Issues and Mathematical Modellingmentioning
confidence: 99%
“…modelling with an environmental focus (Gürbüz & Çalik, 2021;Johnsen-Høines, 2020;Jung et al, 2021;Solares-Rojas et al, 2022).…”
Section: Action and Modellingmentioning
confidence: 99%